Doctor of Physical and Mathematical Sciences, Professor, Academician of the National Academy of Sciences of the Republic of Kazakhstan S.N. Kharin is 80 years old - Ramazanov, M.I. (Bulletin of the Karaganda University. Mathematics Series, 2019)
Doctor of Physical and Mathematical Sciences, Professor, Academician of the National Academy of Sciences of the Republic of Kazakhstan S.N. Kharin turned 80 years old. Stanislav Nikolaevich Kharin is a highly qualified specialist in the field of mathematical modeling of thermophysical and electromagnetic phenomena. S.N. Kharin has more than 300 publications, including 4 monographs and 12 copyright certificates for inventions.